The influence of biodegradable magnesium implants on the growth plate. (15th January 2018) - Kraus, Tanja; Fischerauer, Stefan; Treichler, Stefan; Martinelli, Elisabeth; Eichler, Johannes; Myrissa, Anastasia; Zötsch, Silvia; Uggowitzer, Peter J.; Löffler, Jörg F.; Weinberg, Annelie M.
Graphical abstract: Abstract: Mg-based biodegradable materials are considered promising candidates in the paediatric field due to their favourable mechanical and biological properties and their biodegrading potential that makes a second surgery for implant removal unnecessary. In many cases the surgical fixation technique requires a crossing of the growth plate by the implant in order to achieve an adequate fragment replacement or fracture stabilisation. This study investigates the kinetics of slowly and rapidly degrading Mg alloys in a transphyseal rat model, and also reports on their dynamics in the context of the physis and consecutive bone growth. Twenty-six male Sprague–Dawley rats received either a rapidly degrading (ZX50; n = 13) or a slowly degrading (WZ21; n = 13) Mg alloy, implanted transphyseal into the distal femur. The contralateral leg was drilled in the same manner and served as a direct sham specimen. Degradation behaviour, gas formation, and leg length were measured by continuous in vivo micro CT for up to 52 weeks, and additional high-resolution µCT (HRS) scans and histomorphological analyses of the growth plate were performed. The growth plate was locally destroyed and bone growth was significantly diminished by the fast degradation of ZX50 implants and the accompanying release of large amounts of hydrogen gas. In contrast, WZ21 implants showed homogenous and moderate degradation performance, and the effect on bone growth did not differ significantly from a single drill-hole defect. Statement of Significance: This study is the first that reports on the effects of degrading magnesium implants on the growth plate in a living animal model. The results show that high evolution of hydrogen gas due to rapid Mg degradation can damage the growth plate substantially. Slow degradation, however, such as seen for WZ21 alloys, does not affect the growth plate more than drilling alone, thus meeting one important prerequisite for deployment in paediatric osteosynthesis.